EFFECTIVENESS OF LOCALLY ISOLATED BIOLOGICAL CONTROL AGENTS AGAINST BLACK BLIGHT DISEASE OF DATE PALMS - HANTOOSH, MOHAMMED N.K.; Hussein, H. Z. (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2026)
This study was aimed to isolate the aim of isolating the Trichoderma longibrachiatum and the Bacillus subtilis from healthy date palm root samples and evaluating their antagonistic effectiveness against the two pathogenic fungi Thielaviopsis paradoxa and Thielaviopsis punctulata that cause black scorch in date palm Phoenix dactylifera. The biological control agents T. longibrachiatum and B. subtilis showed efficiency in inhibiting the growth of both pathogenic fungi T. paradoxa and T. punctulata when double cultured in PDA medium. In specific, the T. longibrachiatum inhibited the growth of both pathogenic fungi T. paradoxa and T. punctulata by 50.58 and 60.17%, respectively. While B. subtilis gave an inhibition rate of 39.99 and 38.09%, respectively. The results of detecting secondary metabolite compounds in cultures of the T. longibrachiatum and the B. subtilis using a GC-MS instrument showed that each of them can produce many bioactive compounds. Among these compounds are Hexanoic acid, 1,3-Benzenedicarboxylic acid, bis(2-ethylhexyl) ester, Terephthalic acid, 2-ethylhexyl octyl ester, Heptane, 1-(ethenylthio)- and 4(1H)-Pyrimidinone, 2-(ethylthio).